2011
DOI: 10.1007/s10640-011-9498-2
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment, Human Capital and Environmental Pollution in China

Abstract: By using provincial socioeconomic and environmental data, this paper examines the relationship between human capital, FDI and pollution emissions in China. The result shows the impact of FDI on pollution emission is highly dependent on the level of human capital. FDI is negatively associated with pollution emissions in provinces with the higher levels of human capital, whereas FDI is positively related to pollution emissions in provinces with the lower levels of human capital. This suggests that pollution have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
131
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(143 citation statements)
references
References 51 publications
9
131
1
2
Order By: Relevance
“…Albornoz et al (2009) find that both foreign-owned and domestic firms with linkages with foreign companies are more likely to implement environmental management systems in Argentina, thus supporting positive FDI environmental spillovers. Bao et al (2011) also show that FDI has reduced overall pollution emissions in Chinese provinces, while Lan et al (2012) show that positive FDI environmental spillovers depend on the level of human capital.…”
Section: Fdi and Environmental Spilloversmentioning
confidence: 98%
See 1 more Smart Citation
“…Albornoz et al (2009) find that both foreign-owned and domestic firms with linkages with foreign companies are more likely to implement environmental management systems in Argentina, thus supporting positive FDI environmental spillovers. Bao et al (2011) also show that FDI has reduced overall pollution emissions in Chinese provinces, while Lan et al (2012) show that positive FDI environmental spillovers depend on the level of human capital.…”
Section: Fdi and Environmental Spilloversmentioning
confidence: 98%
“…This dependence also applies to FDI-EKE (Wang and Chen 2014). FDI spillovers can be conditioned by a range of factors, such as local absorptive capability, effective linkages between foreign and domestic firms in the local value chain, a sufficient stock and mobility of local human capital, the level of foreign tangible assets, as well as pace and regularity of the entry process (Crespo and Fontoura 2007;Lan et al 2012;Meyer and Sinani 2009;Wang and Chen 2014). Although the literature specifically addressing the determinants of FDI environmental spillovers is sparse, several attempts have been made to highlight the importance of local capabilities.…”
Section: Regional Dimension Of Fdi Environmental Knowledge Externalitmentioning
confidence: 99%
“…Similarly the study by Cole et al (2011) shows that the entry of the multinational companies in the developing countries are not responsible for increasing pollution in China since these firms used favorable high-tech which are more efficient than the traditional firms in most of the developing countries. Lan et al (2012) examined the relationship between the emission of pollution, inflow of FDI and human capital in China. Findings from the study show that impact of FDI in environmental quality through non ethnic sources in China are not drawn by the lax environmental regulations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is because many previous studies have found that the government's investment in environmental management plays an important role in preventing industrial pollution [32,33]. A possible reason is that more investment in environmental protection technology and management may positively affect sustainable industrial development through energy savings and the reduction of industrial pollutants [34,35]. In fact, the investment in environmental pollution management was formally established in 1980s, and the management of industrial pollution is one of its important goals, e.g., the management of industrial pollution sources and reuse of industrial wastewater.…”
Section: Influencing Factorsmentioning
confidence: 99%